Protection Consumers Against Beauty Salons In Performing Invasive Actions - Devi Fahwi Kurniastuti; Ratna Wulan Valentina; Risky Eka Pratama; Yessa Ayu Agista; Aris Prio Agus Santoso (West Science Law and Human Rights, 2024)
The rapid development of the times not only creates a need related to clothing, food and shelter, but also creates other needs in the form of beauty needs. This is the reason many business actors have begun to switch to offering services in the beauty sector.  There is an overlap regarding the duties and authority of nurses who perform invasive actions in the practice of independent surgery.  This study utilizes a normative legal method as its research foundation in examining beauty salons in Indonesia. This method is known for its emphasis on analyzing written legal norms and related references concerning regulations on beauty and aesthetics. Actions taken by nurses without the supervision of a doctor can be considered a violation of the applicable law. Thus, it is important for the government and consumer organizations to continue to supervise and control beauty salon practices in order to ensure that the services provided comply with consumer health and safety standards. This supervision is also important to prevent unnecessary invasive actions that could potentially harm consumers.